Operation of a Microfabricated Planar Ion-Trap for Studies of a Yb+–Rb Hybrid Quantum System - Bahrami, Abasalt; Mueller, Matthias; Drechsler, Martin; Joger, Jannis; Gerritsma, Rene; Schmidt-Kaler, Ferdinand (physica status solidi (b), 2019)
In order to study interactions of atomic ions with ultracold neutral atoms, it is important to have sub-µm control over positioning ion crystals. Serving for this purpose, a microfabricated planar ion trap featuring 21 DC electrodes is introduced. The ion trap is controlled by a home-made FPGA voltage source providing independently variable voltages to each of the DC electrodes. To assure stable positioning of ion crystals with respect to trapped neutral atoms, the authors integrate into the overall design a compact mirror magneto optical chip trap (mMOT) for cooling and confining neutral 87Rb atoms. The trapped atoms will be transferred into an also integrated chip-based Ioffe-Pritchard trap potential formed by a Z-shaped wire and an external bias magnetic field. The authors introduce the hybrid atom–ion chip, the microfabricated planar ion trap, and use trapped ion crystals to determine ion lifetimes, trap frequencies, positioning ions, and the accuracy of the compensation of micromotion.
CRIS-Team Scopus Importer:2023-03-27
Keywords: atom traps; atom–ion interaction; ion traps